The ADNP Syndrome and CP201 (NAP) Potential and Hope - Gozes, Illana (Front Neurol, 2020)
Activity-dependent neuroprotective protein (ADNP) syndrome, also known as Helsmoortel-Van Der Aa syndrome, is a rare condition, which is diagnosed in children exhibiting signs of autism. Specifically, the disease is suspected when a child is suffering from developmental delay and/or intellectual disability. The syndrome occurs when one of the two copies of the ADNP gene carries a pathogenic sequence variant, mostly a de novo mutation resulting in loss of normal functions. Original data showed that Adnp(+/−) mice suffer from learning and memory deficiencies, muscle weakness, and communication problems. Further studies showed that the ADNP microtubule-interacting fragment NAP (called here CP201) resolves, in part, Adnp deficiencies and protects against ADNP pathogenic sequence variant abnormalities. With a clean toxicology and positive human adult experience, CP201 is planned for future clinical trials in the ADNP syndrome.